Unlocking the potential of stimuli-responsive injectable hydrogels for bone healing applications - Al Mamun, Abdulla; Shamiya, Yasmeen; Hasan, Anwarul; Paul, Arghya (Frontiers in Biomaterials Science, 2025)
Stimuli-responsive, or “smart”, injectable hydrogels respond to real-time stimuli through physical or chemical changes. This allows hydrogels to be dynamic within their environment in the presence of internal or external stimuli. Owing to this, smart injectable hydrogels have gained noticeable implications within the field of biomedicine. Over the past decade, stimuli-responsive injectable hydrogels have been extensively studied for wound healing and cancer therapies but remain largely unexplored for bone healing applications. In this mini-review, we aim to explore the role of smart injectable hydrogels and assess their current and future implications within the field of bone healing. Specifically, we discuss the physicochemical and biological aspects that must be taken into consideration when developing a material in this field, as well as the various strategies for designing such a material. Additionally, we discuss the current role of stimuli-responsive injectable hydrogels for an array of bone healing applications and their potential for successful clinical translation.